Dielectric properties of chili powder in the development of radio frequency and microwave pasteurisation. (31st December 2017) - Li, Yukun; Zhou, Liangfu; Chen, Jiajia; Subbiah, Jeyamkondan; Chen, Xiangwei; Fu, Hongfei; Wang, Yunyang
ABSTRACT: Food products are dielectric materials. The ability to store and dissipate electromagnetic energy of food in dielectric heating is determined by its dielectric properties. To develop pasteurisation protocols based on radio frequency (RF) and microwave (MW) heating of chili powder, dielectric properties of chili powder were measured using an open-ended coaxial-line probe and an impedance analyzer over a frequency range from 8 to 3000 MHz. Penetration depth of chili powder was calculated at five selected frequencies. Results showed that the dielectric properties of chili powder decreased with increase in frequency from 8 to 3000 MHz, but increased with increase in moisture content from 4 to 15% (w. b.) and with increase in temperature from 25 to 85°C. Dielectric constant and loss factor of different density samples showed little difference at low temperature, but large difference at high temperature. RF waves have larger penetration depth in chili powder than MW, and therefore could result in better heating uniformity especially for thicker samples during pasteurisation process. Geometry of sample and heating runaway phenomena may also affect the application of RF pasteurisation for foods. The relationship between moisture content, temperature, and dielectric properties of chili powder at 13.56, 27.12, 40.68, 915 and 2450 MHz can be described by third-order polynomial models with high coefficient of determination ( R 2 >0.89), which can be used to predict temperature- and moisture-dependent dielectric constant and loss factor of chili powder with high accuracy.